Modernization of Technology and Organization of Production of Triethylaluminium Co-Catalyst for Olefin Polymerization - Tumasev R. V.; Arkatov O. A.; Goryaynov M. A.; Dudchenko V. K.; Mayer E. A. Eduard Aleksandrovich; Pestryakov A. N. Aleksey Nikolaevich (2013, 2013)
Title screen